¿Por qué es clásica la teoría clásica? Teorizando el canon y canonizando a Du Bois. - Burawoy, Michael (Universidad Icesi, 2022)
Uno de los debates más polémicos que atraviesa a la sociología es qué hacer con el canon de Marx, Weber y Durkheim: ¿abandonarlo, comenzar con uno nuevo o reconstruir el existente? En este artículo examino las afirmaciones de Connell, la principal defensora de la idea de abandonar el canon. Ella afirma que este es una imposición arbitraria que no tiene relación con la historia real de la sociología y que sería mejor que examináramos cómo el canon llegó a serlo. Ella no considera el valor intrínseco del canon y, en cambio, propone la idea de la teoría del Sur. No está claro qué es lo que caracteriza a una teoría tal ni qué es lo que reúne al conjunto de teóricos que se proponen como parte de ella. Como alternativa propongo reconstruir el canon con la vida y obra de W.E.B. Du Bois, quien fue impulsado precisamente por los temas que preocupan a Connell. El canon es relacional, de modo que Du Bois no se agrega simplemente, sino que se pone en conversación con Marx, Weber y Durkheim, lo que lleva a una relectura de cada uno de estos teóricos.

One of the most contentious debates coursing through sociology is what to do with the canon of Marx, Weber, and Durkheim: abandon the canon, start afresh with a new canon, or reconstruct the existing canon? In this paper I examine the claims of Connell, the foremost advocate of abandoning the cannon. She claims the canon is an arbitrary imposition that bears no relation to the actual history of sociology and we would be better off examining how the canon came to be. She does not consider the intrinsic value of the canon and instead advances the idea of Southern theory. It is not clear what is Southern about Southern theory nor what holds together the array of theorists she proposes. As an alternative I propose reconstructing the canon with the life and work of W.E.B. Du Bois who was propelled by precisely the issues that concern Connell. The canon is relational so that Du Bois is not simply added but brought into conversation with Marx, Weber, and Durkheim, leading to a rereading of each theorist. The canon has always been subject to revision when it atrophies, when it moves out of sync with questions raised by the world and by sociology. I agree with others that contemporary questions push Du Bois to the forefront—however, not at the expense of Marx, Weber, and Durkheim but in di-alogue with them. I outline a possible direction of such dialogues from which all would benefit. Just as the inclusion of Marx had dramatic consequences for the recalibration of Weber and Durkheim, so the same will happen with the inclusion of Du Bois with regard to Weber, Durkheim, and Marx, and, at the same time, stiffening and advancing a Du Boisian sociology. Incorporating Du Bois into the existing canon may appear to be a reformist move but if attention is paid to the whole gamut of Du Bois’s oeuvre, then the consequences could be revolutionary, even to the point of sidelining one or more of Marx, Weber, and Durkheim.
Why is classical theory classical? Theorizing the canon and canonizing Du Bois.
Keywords: Canon (Literature); Sociology; Classical school of economics; Marxian school of sociology; Canon; Canon; Sociología clásica; Sociología clásica; Durkheim; Durkheim; Du Bois; Du Bois; Marx, Weber; Marx, Weber; Canon (Literatura); Sociología; Escuela de pensamiento económico clásico; Escuela marxista de sociología; http://id.loc.gov/authorities/subjects/sh85019643; http://id.loc.gov/authorities/subjects/sh85124200; http://id.loc.gov/authorities/subjects/sh85026712; http://id.loc.gov/authorities/subjects/sh85081690; Sociología; Sociology; Marxismo; Marxism; http://vocabularies.unesco.org/thesaurus/concept382; http://vocabularies.unesco.org/thesaurus/concept5855; Sociología; Sociology; Marxismo; Marxism; Sociología; Sociology; Marxismo; Marxism; Z13 Economic sociology; B14 Socialist; B14 Marxist